Annotated record of the detailed examination of Mn deposits in lake Humaljärvi, Finland - K M Levander (PANGAEA, 1906)
The Humaljärvi lake is situated 25 km West of Helsinki (formely, Helingsfors). The author proceeded to dredge the bottom of the lake in order to study its plancton species following a preceeding study of Pr. J. E. Rosberg in 1900. From the middle of the lake, at a maximum depth of about 10 meters the dredge brought easily some fairly soft gray mud. When the mud samples were sifted, it remained sand grains and ferro-manganese deposits in the form of abundant small round or lenticular objects, 2-6 mm in diameter.
Supplement to: Levander, KM (1906): Über das Plankton des Sees Humaljärvi = About the plankton of Lake Humaljärvi. In: Meddelanden, Societas Pro Fauna Et Flora Fennica - Trettiondeandra Häftet 1905 - 1906. Helsingfors, Finland, 42-46, https://archive.org/details/meddelandenafsoc320506soci